Perilaku Sosial Dalam Konteks Pendidikan Multikultural - Saputra, Erwin Eka; Parisu, Chairan Zibar L. (Jurnal Konseling dan Psikologi Indonesia, 2025)
Multicultural education plays an important role in shaping the social behavior of students who are able to appreciate the diversity of cultures, religions, and values. This education not only aims to increase knowledge about diversity, but also to instill attitudes of empathy, tolerance, and social solidarity. This study examines the relationship between multicultural education and the formation of students' social behavior through the literature study method by analyzing various primary and secondary sources. The results of the study indicate that a multicultural education approach integrated into the curriculum can help students understand and respect differences, thereby creating inclusive social interactions. In addition, strategies such as class discussions, cross-cultural collaboration, and critical reflection are effective in building students' social awareness. By developing multicultural education, schools contribute to the creation of a harmonious society free from prejudice. This shows the importance of implementing multicultural education as a whole in the world of education.